Effect of recruitment and selection practices on organisational strategic goals - Anita Bans-Akutey; Attahiru Muhammed Abdullahi; Emelia Ohene Afriyie (Annals of Management and Organization Research, 2021)
Purpose: This study aimed at examining how recruitment and selection practices influence organisational strategic goals. Research methodology: A descriptive case study design was employed. Data was collected from 311 employees of Nestle Water Company who were randomly selected. Results: The study showed that screening affects profitability and market share positively though the effects were insignificant. The selection test on the other hand affects profitability both positively and significantly. There was however a positive insignificant relationship between the selection test and market share. Lastly, the study showed that there exists a positive significant relationship between e-recruitment and profitability; as well as e-recruitment and market share of Nestle water company. Limitations: This study focused on just four recruitment and selection tools as well as employees of Nestle water company. Contribution: The general assertion of scholars that screening, selection tests, e-recruitment, and employee referral have the capacity to stimulate an increase in the profitability and market share of an organisation was confirmed. It is recommended that future studies consider other recruitment and selection tools which were not considered in this study.